Effects of early maternal cancer and fertility treatment on the risk of adverse birth outcomes. (April 2022) - Everhøj, Cathrine; Norsker, Filippa Nyboe; Rechnitzer, Catherine; Licht, Sofie de Fine; Nielsen, Thomas T; Kjær, Susanne K.; Jensen, Allan; Hargreave, Marie; Christensen, Jane; Belmonte, Federica; Urhoj, Stine Kjaer; Strandberg-Larsen, Katrine; et al.
Summary: Background: Early maternal cancer and fertility treatment each increase the risk for adverse birth outcomes, but the joint effect of these outcomes has not yet been reported. Thus, the aim was to assess the individual and joint effect of maternal cancer and fertility treatment on the risk for adverse birth outcomes. Methods: This population-based cohort study included 5487 live-born singletons identified in the Danish Medical Birth Register (1994–2016) of mothers with previous cancer (<40 years) recorded in the Danish Cancer Registry (1955–2014). We randomly selected 80, 262 live-born singletons of mothers with no cancer <40 years matched to mothers with cancer by birth year and month. We calculated odds ratios (ORs) for preterm birth, low birth weight (LBW) (<2500 g) and small for gestational age (SGA), mean differences in birth weight in grams, and additional cases of preterm birth (gestational age<259 days) per 100, 000 person-years. Multiplicative and additive interaction of maternal cancer and fertility treatment was compared with outcomes of children conceived naturally to mothers with no maternal cancer (reference group). Findings: Among 84, 332 live-born singletons, increased ORs for preterm birth were observed among children born to mothers with previous cancer (1·48, 95% confidence interval [CI] 1·33–1.65) or after fertility treatment (1·43, 95% 1·28–1–61), with 22 additional cases of preterm birth among both group of children (95% CI 15–29; 95% CI 14–30). In the joint analyses, the OR for SGA for children born after fertility treatment to mothers with previous cancer was similar to that of the reference group (OR 1·02, 95% CI 0·72–1·44, P for interaction=0·52). Children with both exposures had increased ORs for LBW (1·86, 95% CI 1·17–2·96, P for interaction=0·06) and preterm birth (2·31, 955 CI 1·66–3·20, P for interaction = 0·56), with 61 additional cases of preterm birth (95% CI 27–95, P for interaction=0.26) over that of children in the reference group. The mean birth weight was also lower in children born to mothers with both exposures (-140 g, 95% CI -215; -65) ( P for interaction=0.06) but decreased to -22 g (95% CI -76; 31) after adjustment for GA. Interpretation: Although we did not find any statistically significant additive interaction between maternal cancer and fertility treatment, children born after fertility treatment of mothers with previous cancer were at increased risk for adverse birth outcomes. Thus, pregnant women with both exposures need close follow-up during pregnancy. Funding: The Danish Cancer Society and the Danish Childhood Cancer Foundation.